Development and Teaching Application of Interactive Virtual Algorithm Animation of C Language Program - Wan, Lei; Cao, Yongli; Shi, Lili; An, Ying (Computational intelligence and neuroscience, 2022)
In today’s world, almost every domain has certain and mandatory requirements to understand at least one of the programming languages which is defined as a way of interaction with a computer to resolve real world problems or more specifically for the implementation of algorithms. Language programming is a course with strong theory and practice. In view of the fact that C language beginners in colleges and universities generally report that it is difficult to learn well due to various reasons. Therefore, in this paper, we have discussed the development and teaching of interactive virtual animation of C language programs. The proposed approach relies on a typical recursive algorithm case to analyze the teaching strategy of virtual algorithm animation brought into the classroom, the application in the algorithm teaching of C language and the teaching strategy in improving students’ understanding of abstract knowledge using computer C language program interactive virtual animation development and implementation of the teaching system is the research content. According to the basic flow of the interactive virtual algorithm of the C language program, a reasonable system structure design is carried out.